A water-soluble near-infrared fluorescent probe for specific Pd2+ detection. Issue 4 (15th February 2018) - Wen, Jia; Lv, Yinghua; Xia, Pengyi; Liu, Fengyu; Xu, Yongqian; Li, Hongjuan; Chen, Su-Shing; Sun, Shiguo
Graphical abstract: A novel near-infrared fluorescent probeM-PD has been developed for selective detection of Pd 2+ based on naphthofluorescein. Abstract: Palladium (Pd) is widely used in chemistry, biology, environmental science etc ., and Pd 2+ is the most plenitudinous oxidation state of the Pd that can exist under physiological conditions or in living cells, which could have adverse effects on both our health and environment. Thus, it is of great significance to monitor the changes of Pd 2+ . Hence, a novel near-infrared fluorescent probeM-PD has been developed for selective detection of Pd 2+ based on naphthofluorescein in this work. The result demonstrated thatM-PD exhibited favorable properties for sensing Pd 2+ such as excellent water solubility, high selectivity and sensitivity. And the limit of detection was estimated as 10.8 nM, much lower than the threshold in drugs (5–10 ppm) specified by European Directorate for the Quality Control of Medicines. More importantly, detection and recovery experiments of Pd 2+ in aspirin aqoeous solution and soil are satisfactory. In addition, M-PD has also been successfully used for near-infrared fluorescence imaging of Pd 2+ in living cells, indicating that the probe has better feasibility and application potential in the determination of Pd 2+ .